2022
DOI: 10.1371/journal.pgph.0000167
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to care and community health in Haiti with optimized community health worker placement

Abstract: The national deployment of polyvalent community health workers (CHWs) is a constitutive part of the strategy initiated by the Ministry of Health to accelerate efforts towards universal health coverage in Haiti. Its implementation requires the planning of future recruitment and deployment activities for which mathematical modelling tools can provide useful support by exploring optimised placement scenarios based on access to care and population distribution. We combined existing gridded estimates of population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 33 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…5,18,[23][24] However only three previous studies have used geospatial analysis to assess the efficiency of CHW deployment at national scale using robust modelling approaches. [20][21][22] Champagne et al compared the efficiency of various CHW deployment scenarios in terms of optimising geographic coverage of the estimated population in Haiti. 22 five deaths, and Pf malaria cases, respectively, and found that the existing CHW networks were inefficiently deployed across all three targeting metrics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,18,[23][24] However only three previous studies have used geospatial analysis to assess the efficiency of CHW deployment at national scale using robust modelling approaches. [20][21][22] Champagne et al compared the efficiency of various CHW deployment scenarios in terms of optimising geographic coverage of the estimated population in Haiti. 22 five deaths, and Pf malaria cases, respectively, and found that the existing CHW networks were inefficiently deployed across all three targeting metrics.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Champagne et al compared the efficiency of various CHW deployment scenarios in terms of optimising geographic coverage of the estimated population in Haiti. 22 five deaths, and Pf malaria cases, respectively, and found that the existing CHW networks were inefficiently deployed across all three targeting metrics. 20,21 However, unlike our study, these previous studies did not compare the efficiency of approaches for optimising the scale and deployment of CHWs nationally across each of these outcomes of interest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations